2013
DOI: 10.1074/jbc.m113.455451
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleic Acid-binding Domain and Translational Repression Activity of a Xenopus Terminal Uridylyl Transferase

Abstract: Background: TUT7 adds uridines to and regulates RNAs. Results: Xenopus TUT7 (XTUT7) uridylates RNAs, possesses a basic region that binds nucleic acids, and represses translation of a polyadenylated RNA. Conclusion: XTUT7 contains a nucleic acid-binding domain important for activity and can repress translation. Significance: The basic region of XTUT7 may bind RNA in vivo. XTUT7 may control mRNAs by occluding poly(A).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 69 publications
0
28
0
Order By: Relevance
“…Consequently, UTP selectivity of Gld2, which is phylogenetically derived from Tut4/7 (Fig. 5), is conferred by a histidine insertion, rather than an Asn to His mutation as previously suggested (Lunde et al 2012;Yates et al 2012;Lapointe and Wickens 2013).…”
Section: Convergent Evolution Of Tutase Activity By Histidine Insertimentioning
confidence: 78%
See 2 more Smart Citations
“…Consequently, UTP selectivity of Gld2, which is phylogenetically derived from Tut4/7 (Fig. 5), is conferred by a histidine insertion, rather than an Asn to His mutation as previously suggested (Lunde et al 2012;Yates et al 2012;Lapointe and Wickens 2013).…”
Section: Convergent Evolution Of Tutase Activity By Histidine Insertimentioning
confidence: 78%
“…In Cid1, histidine 336, which is located on a flexible loop near the catalytic site, sterically excludes ATP from the active site. Prior experiments have shown that mutation of this histidine to a smaller amino acid broadens nucleotide specificity in uridylyltransferases to include ATP, concluding that an asparagine to histidine mutation confers ATP specificity (Lunde et al 2012;Yates et al 2012;Lapointe and Wickens 2013). Our multiple sequence alignment ( Fig.…”
Section: Convergent Evolution Of Tutase Activity By Histidine Insertimentioning
confidence: 99%
See 1 more Smart Citation
“…If storage of mRNAs in P-bodies is regulated by uridylation, deuridylation should be required for reentry of the stored mRNAs into polysomes, suggesting that uridylation is involved in translational inactivation. Indeed, uridylated poly(A) + reporter luciferase RNA is translationally inactive in Xenopus oocytes (Lapointe and Wickens 2013). Therefore, modification of the 3 ′ oligo(U) tail in starfish oocytes may translationally inactivate certain mRNAs prior to hormonal stimulation.…”
Section: Mrna Stabilization and Decay In Oocytesmentioning
confidence: 99%
“…Moreover, uridylation of the 3 ′ end of a polyadenylated luciferase reporter RNA represses translation of the RNA in Xenopus oocytes (Lapointe and Wickens 2013).…”
Section: Introductionmentioning
confidence: 99%